Political Uses of the Concept of Human Security: Securitization of the Violation of Human Rights and Underdevelopment in the International Scenario - Muñoz Tejada, Julián Andrés (Universidad del Rosario, 2018)
In this article, a documentary review is made about some political uses of the concept of human security in the international scenario. The article shows how these uses in the international scenario were concretized in securitization processes around the violation of human rights and of underdevelopment in some contexts. It explores how clearly differentiable human security discourses were formed, which confirms the equivocal nature of the concepts in politics, and how to study the uses that specific actors gave them in specific contexts can know their meanings.